Features of the course of measles in adults - I. A. Ivanova; Zh. B. Ponezheva; M. S. Kozlova; E. T. Vdovina; N. A. Tsvetkova (Лечащий Врач, 2021)
The article presents a modern understanding of measles — the epidemiology of the disease, brief data on the tactics of treatment of pathogenesis, clinic and patient management. A clinical example of measles in an adult is presented. The article reflects the modern approaches to the diagnosis and prevention of this highly contagious infection.